Finite element analysis and automation of a medium scale grinder applied to the manufacture of cassava starch - Oroun’Gobi, Idayatou; Guo, Chen Guang (Frontiers in Mechanical Engineering, 2024)
This research is based on the modeling, internal structure analysis, and automation of a cassava grinding machine. For the design, the single-cylinder grinder was chosen due to its advantages, notably simplicity and versatility. The grinding method used in this type of grinder is compression. The mechanical design and simulation software first allowed for the design of the grinder and then for performing static analyses under three loads (P1 = 10000N, P2 = 15000N, and P3 = 20000N). The results of these tests led to the selection of P3 = 20000N as the straightening load, with a maximum stress value in the static analysis of 88,18 MPa and a maximum deformation of 0,000358 under the force of load P3. Additionally, the frequency analysis distinguished five resonance modes. The results for each mode concluded that no resonance would affect the machine, thus ensuring stable operation. Furthermore, fatigue, frequency, and safety factor studies showed that the machine could withstand a load of m3 = 2000 kg without damage, with a service life of 1e+09 cycles. Considering the total number of life cycles, which is 1e+09 cycles, this means that the machine will have a service life of 347000 years, with a total grinding output of 2e+12 kg of cassava and 5840000 kg per year. The factor of safety is FoS = 1,78, indicating a sufficient margin for safe operating conditions. The automation of the grinder was carried out using a GRAFCET model and a sophisticated human-machine interface (HMI), providing an additional safety point for the machine and allowing the operator to monitor the operation via a simple graphical interface. This automation enables continuous operation with minimal human intervention, thereby improving the efficiency and safety of the cassava grinding process.